Shazam! [videorecording (DVD)] - Gayden, Henry; Lemke, Darren; Levi, Zachary, 1980-; Strong, Mark, 1963-; Angel, Asher, 2002-; Grazer, Jack Dylan, 2003-; Hounsou, Djimon, 1964-; Good, Meagan, 1981-; Wallfisch, Benjamin; Alexandre, Maxime, 1971- (Warner Bros. Home Entertainment, 2019)
By shouting out one word, streetwise fourteen-year-old foster kid Billy Batson can turn into adult superhero Shazam (aka Captain Marvel), courtesy of an ancient wizard. Still a kid at heart, but inside a ripped, godlike body, Billy revels in this adult version of himself having fun with his superpowers. But he'll need to master these powers quickly to fight the deadly forces of evil.